Investigation of solar air heater optimization with spherical Rib - Ahmed, Abduljabbar Muttair (Edelweiss Applied Science and Technology, 2025)
One clean and environmentally beneficial energy source is solar power. Transparent collector solar air heaters (SAH) are a prime example of the technology currently being researched for use in warming homes and offices. Spherical ribs with three groups of diameters (2, 2.5, and 3 mm) and a relative pitch P/e = 12 for each one. Heat flux from solar energy is 1000 W/m2 for both shapes if a smooth absorbent plate and roughened rib are used. The flow rate at the inlet is determined from the range of values for the Reynolds number (5000 – 15000). A k-ɛ turbulence model and ANSYS Fluent have been used for the numerical simulation. The Nusselt number, friction factor, and heat transfer coefficient values have all been determined. The velocity vector and temperature contour give the flow behavior inside the collector. For the Reynolds number range of 5000–15000, the thermohydraulic factor performance (THPF) can be enhanced up to 2.3. Including spherical ribs across the absorber plate improves the SAH's thermal performance. The suggested artificially roughened surface is advantageous for low domain Reynolds numbers because the maximum enhancement of the THPF value has been found in a region of low Reynolds numbers.